Polymicrobial infections with specific Actinomyces and related organisms, using the current taxonomy - Könönen, Eija (Taylor & Francis, 2025)
Actinomyces organisms reside on mucosal surfaces of the oropharynx and the genitourinary tract. Polymicrobial infections with Actinomyces organisms are increasingly being reported in the literature. Since these infections differ from classical actinomycosis, lacking of specific clinical and imaging findings, slow-growing Actinomyces organisms can be regarded as contaminants or insignificant findings. In addition, only limited knowledge is available about novel Actinomyces species and their clinical relevance. The recent reclassifications have resulted in the transfer of several Actinomyces species to novel genera Bowdeniella, Gleimia, Pauljensenia, Schaalia, or Winkia. The spectrum of diseases associated with specific members of Actinomyces and these related genera varies. In human infections, the most common species are Actinomyces israelii, Schaalia meyeri, and Schaalia odontolytica, which are typical inhabitants of the mouth, and Gleimia europaea, Schaalia turicensis, and Winkia neuii. In this narrative review, the purpose was to gather information on the emerging role of specific organisms within the Actinomyces and related genera in polymicrobial infections. These include Actinomyces graevenitzii in pulmonary infections, S. meyeri in brain abscesses and infections in the lower respiratory tract, S. turicensis in skin-related infections, G. europaea in necrotizing fasciitis and skin abscesses, and W. neuii in infected tissues around prostheses and devices. Increased understanding of the role of Actinomyces and related species in polymicrobial infections could provide improved outcomes for patient care.